ENHANCING TRANSLATION EDUCATION WITH RATPRO: A CAT TOOLS-BASED LEARNING MODEL - Pramawati, Anak Agung Istri Yudhi; Agus Pramerta, I Gde Putu; Erawan, Dewa Gede Bambang (English Review: Journal of English Education, 2024)
The translation process greatly determines the translation results. The translated text should have the same meaning as the source text but still maintain the natural elements. A creative translation model that can help translators produce good translations that have equivalence in meaning and good grammar is essential, considering that the translation process is not just a change of language but is a process of transferring meaning from the source language to the target language (Indonesian-English). RATPro  (Read, Analyze, Transfer, Produce) Translation Model that is based on Computer Assisted Translation (CAT) Tools can be used as a creative and innovative translation model that can help translation students transfer the language of scientific article manuscripts from the source language to the target language while maintaining the equivalence of meaning and naturalness of the language through excellent and correct grammar. RATPro  (Read, Analyze, Transfer, Produce) Translation Model based on Computer Assisted Translation (CAT) Tools can also make it easier for students to translate because it is based on digital recording. This research aims to develop a RATPro translation model based on Computer Assisted Translation (CAT) Tools that are creative and innovative in translating scientific articles by students. The research model used is Research and Development (RnD), where research data is analyzed critically and validated to obtain valid and reliable results. The designedtranslation model will also be well used in translating authentic manuscripts in different manuscript fields.